Konsep Penataan Sistem Sirkulasi Pasar Sentral Makassar Berdasarkan Tingkat Vitalitas - St. Tiefryna Fahlisyah; Ria Wikantari; Riekje Hehanusa Pangkerego (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2015)
The development around the shopping center area occurred quite rapidly and caused a fairly large pull which was marked by the number of trips to the shopping center. This of course raises problems in the shopping center area, especially the problem of circulation. This study aims to assess the level of vitality, identify the condition of the circulation system and develop the concept of structuring the direction of the Makassar Central Market circulation system. The data used were sourced from direct observation, interviews, and literature studies. The analytical method used is quantitative and qualitative descriptive analysis. Based on the results of the analysis conducted, the level of vitality of the Central Market is very high, which of course directly affects the condition of the Central Market circulation system. Traffic jams often occur in this area due to poor traffic management. Conflicts occur between private vehicles and public transportation, vehicles with pedestrians, vehicles with street vendors, and conflicts between the flow of goods and the flow of visitors. The concept of structuring the circulation system in the Central Market area refers to the concept of Travel Demand Management (TDM), where the main strategy is to reduce the use of motorized vehicles, increase the mode of walking and cycling as well as increase the use of high occupancy vehicles.